Measuring the thermal energy performance gap of labelled residential buildings in Switzerland. (February 2020) - Cozza, Stefano; Chambers, Jonathan; Patel, Martin K.
Abstract: This paper addresses the thermal Energy Performance Gap (EPG), defined as the difference between a building's theoretical and actual energy consumption for thermal purposes (heating and hot water). Successful energy policies require estimates of the energy saving potential of the building stock. It is the objective of this work to analyse whether and to what extent an EPG exists in residential buildings in Switzerland. The database of the Swiss Cantonal Energy Certificate for Buildings was used, covering over 50 000 buildings. The median EPG was found to be −11% (i.e. actual consumption lower than theoretical) but varied across ratings from 12.4% (B-label) to −40.4% (G-label). Buildings with low energy ratings tend to consume significantly less than expected, while buildings with high rating tend to consume slightly more than expected. For the A-labels buildings (0.5% of the total) an EPG of −6.2% was found, suggesting that the very high-performance buildings may be more robust to the EPG. Simplified scenarios to illustrate the impact of this EPG on total consumption are presented, which highlight the challenge of meeting the Swiss Energy Strategy 2050 with a realistic renovation rate. The importance of low carbon heat supply for buildings is also discussed. Highlights: Actual consumption for thermal use in Swiss dwellings is somewhat lower than expected. Buildings with poor thermal performance consume substantially less than expected. Buildings with high thermal performance consume somewhat more energy than expected. A range of consumption was observed among buildings with identical energy rating. It is impossible to achieve the energy objectives set with the current renovation rate.